Sistema de numeração e pinturas corporais Javaé: a etnomatemática por uma relação dialógica entre cultura e educação escolar - Ramos, Gabriela Camargo (2016)
The objective of this study was to understand and systematize Javaé’s ethnomathematics knowledge and promote reflection on the integration of these knowledges in indigenous school from the view of indigenous teachers; basing the analysis on the reflections of the Ethnomathematics program, interculturalism, the Decoloniality and ecology of knowledges. The research was conducted in three stages in the Canoanã village located on Ilha do Bananal, Formoso do Araguaia (TO), where it was possible to observe and understand more comprehensively the Javaé cultural context and the reality of Taina indigenous school. After the moment of analysis, a new field work was made in order to promote a debate with indigenous teachers for discuss the importance of Javaé’s ethnomathematics knowledge in indigenous schools. From the results achieved in the research are presented and analyzed Javaé’s ethnomathematics knowledge related to the numbering system and body painting; also was incorporated to the work the discussions about the importance of these own knowledges in Javaé indigenous school.